Doctor Workforce Attrition: Doctor Workplace Attrition: An examination of pathways from work demands to organisational commitment - Michael Ireland; Michelle Engel; Sonja March; Sonali Parmar; Bonnie Clough; Aaron Sharp; Lauren Moses (Asia Pacific Journal of Health Management, 2022)
Health workforce shortages worldwide are approaching crisis point, further burdening systems already struggling to meet demand.  Doctor attrition has been identified as a major contributor to this problem and therefore, the current study examined links between workload demands and stressors, and doctors’ commitment. Based on prior research and key psychological theories, pathways were hypothesised that were initiated by workload demands and stressors, proceeding through work-life conflict and psychological distress, intrinsic motivation factors, through to commitment.  A sample of 208 medical doctors completed self-report measures of these constructs. Among workload hassles and demands, quantitative demands, representing the extent that workload exceeds available resources (e.g., time) emerged as the strongest predictor.  Meaningfulness of work was the strongest direct predictor of commitment, followed by work-life conflict, job satisfaction and burnout. This study highlights the importance for workplaces providing an environment that nurtures doctors’ intrinsic motivation and manages doctor workloads to ensure work-life balance is maintained.